Detecção e identificação de beta-lactamases de espectro estendido e de genes de resistência às quinolonas em Enterobacteriaceae isoladas de amostras de carnes de frango, suína e bovina destinadas ao consumo humano - Takahashi, Juliana Tiemi (2015)
Introduction: Bacterial resistance to antimicrobials is an important public health problem, which results in increased treatment period, increase in mortality and in health care costs. This phenomenon is considered a result of the indiscriminate use of antimicrobials in human and veterinary medicine, and along the food chain. In recent years, it has been observed the frequent isolation of resistant bacteria from animal production and food of animal origin. In this context, have been highlighted the resistance to beta-lactâmicos and to quinolones, the first, due to extended-spectrum beta-lactamase (ESBL) production and the second, resultant from the acquisition of qnr genes encoding proteins that interfere in quinolone action on DNA gyrase and topoisomerase IV. Several bacterial species with antimicrobial resistance have been isolated from farm animals. Objective: This study evaluated the antimicrobial susceptibility profile and the presence of resistance genes blaCTX-M, blaSHV, blaTEM, qnrA, qnrB, qnrS and oqxAB in Enterobacteriaceae isolated from meat market in the municipality of São José do Rio Preto- SP, acquired between November 2010 and August 2012. Material and Methods: The antimicrobial susceptibility was determined by disk diffusion according to CLSI. Strains resistant to beta-lactams and quinolones were submitted to PCR using specific primers for detection and sequencing of these genes for identification. Results: A total of 75 isolates were resistant to beta-lactam and 125 to quinolones. Among these, 6.6% blaCTX-M, 6.6% blaTEM, 16% blaSHV, 21.6% had qnr variants and 13.6% oqxAB. In a strain of Aeromonas sobria was detected the coexistence of qnrA and qnrS genes; the qnrB gene was detected in five strains of E. coli, five K.pneumoniae, two Salmonella spp. and 12 Citrobacter spp. The qnrB19 gene was detected in two K. pneumoniae, duas E. coli and one Citrobacter braakii. qnrB2 was detected in three K. pneumoniae. The qnrS1 gene was detected in a strain of K. pneumoniae. The sequencing blaCTX-M revealed blaCTX-M-2, all of which were derived from chicken meat samples. Conclusion: These data demonstrate there nay be association between excessive use of antimicrobials in animal production and isolation of bacteria resistant to these antimicrobials. The presence of bacteria resistant to antimicrobials in meat intended for human consumption consists in a public health problem and can affect commercials relationships of the country, since it the Brazil is one of the world's largest meat exporters.